A checklist of Zingiberaceae species from Mt. Hamiguitan Range Wildlife Sanctuary, Davao Oriental, Philippines - Naive, Mark Arcebal Kling (Journal of Tropical Life Science, 2021)
Mount Hamiguitan Range Wildlife Sanctuary is a center of botanical diversity throughout the Philippine archipelago. However, as to how many Zingiberaceae species are present in the area is still unknown. Thus, floristic surveys were made and collections were conducted from July 2016 to September 2018. In total, 16 species belonging to eight genera representing three tribes of the family were recorded. The most species rich tribe belongs to Alpinieae with 13 species in 5 genera. This study presents a checklist of Zingiberaceae species found in the sanctuary which is beneficial for its efficient biological resource mangement.Â